2008
DOI: 10.1111/j.1939-3938.2007.tb00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Women's Perceptions of the Impact of a Domestic Violence Treatment Program For Male Perpetrators

Abstract: This qualitative descriptive study examined women's perceptions of a court mandated batterer treatment program that their spouse or partner participated in following arrest for domestic violence. Although the women felt treatment had a positive impact on several factors, their feedback helped identify possible improvements in batterer treatment programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…The findings of this study show that most male and female participants reported positive changes for themselves as individuals and for their relationships during the course of therapy. A previous study by Hayward et al (2007), interviewing a select group of eight partners of men who participated in a BIP, also found that these women believed that completing the BIP improved their relationships, however, the study also highlighted participants' perceptions that continued treatment after the BIP was most helpful in improving the relationships. One common rationale for limiting the use of couples therapy has to do with the belief that it minimizes offenders' accountability for the violence (e.g., Avis, 1992).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The findings of this study show that most male and female participants reported positive changes for themselves as individuals and for their relationships during the course of therapy. A previous study by Hayward et al (2007), interviewing a select group of eight partners of men who participated in a BIP, also found that these women believed that completing the BIP improved their relationships, however, the study also highlighted participants' perceptions that continued treatment after the BIP was most helpful in improving the relationships. One common rationale for limiting the use of couples therapy has to do with the belief that it minimizes offenders' accountability for the violence (e.g., Avis, 1992).…”
Section: Discussionmentioning
confidence: 74%
“…Critics of couples treatment for IPV often express concern that including female victims in treatment with their male partners may disempower them and make them feel responsible for their partners' violence (e.g., Avis, 1992). Interestingly, in the qualitative study conducted by Hayward et al (2007), a central theme expressed by victims of violence whose husbands participated in a BIP program was self-blame. In that study, participants continued to take partial blame for their partners' actions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some programmes were primarily prevention-focused and aimed at high schools or colleges (Jaime et al, 2018), while others were aimed at individuals who were at risk of, or had engaged in, violent behaviours. The interventions reported by these studies include working with couples to improve relationship skills (Kalokhe et al, 2019); teaching self-regulation techniques (Wistow, Kelly, & Westmarland, 2017); stopping violence group education (Hayward, Steiner, & Sproule, 2007); and peer support groups (Casey, Leek, Tolman, Allen, & Carlson, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A more interactive health promotion resource was designed to accompany the poster and act as a tool to promote 'time out' and self-regulating strategies. References in the literature to men "taking time out" to go for a drive (Hayward et al, 2007) led us to create a keychain with a traffic light image designed to communicate a 'stop, think, share' strategy to help de-escalate tense situations and promote support-seeking. Contact details for support services were listed on the back of the keychain.…”
Section: Health Promotion Resources: Poster and Keychainmentioning
confidence: 99%